Handbook of communication and emotion research, theory, applications, and contexts - Andersen, Peter A.; Guerrero, Laura K. (Academic Press, 1996)
Emotion is once again at the forefront of research in social psychology and personality. The Handbook of Communication and Emotion provides a comprehensive look at the questions and answers of interest in the field: How are specific emotions (fear, jealousy, anger, love) communicated? How does the effectiveness, or ineffectiveness, of this communication affect relationships? How is the communication of emotion utilized to deceive, or persuade, others? This important reference work is edited by top researchers in the field of communication and authored by a who's who in emotion and communication.--Provided by publisher.